The Interaction Between Classroom Management and Arabic Teaching Approaches at Pondok Modern Al-Kautsar Pekanbaru - Aidil Azza Mu'izzuddin; Lia Mahardika Harahap; Erka Pulungan; Hakmi Wahyudi; Siti Sumaiah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Despite growing attention to communicative language teaching, research on classroom interaction management in modern Islamic boarding schools (pesantren) remains scarce, as the unique dormitory-based language environment presents challenges distinct from regular school settings. This study aims to analyze classroom interaction management and Arabic language teaching approaches at Pondok Modern Al-Kautsar Pekanbaru. A qualitative descriptive design was employed, with data collected through participatory observation, in-depth interviews, and documentation. Research participants consisted of two Arabic language teachers and twelve students selected purposively. The findings indicate that: (1) teachers implement a phased interaction pattern moving from one-way explanation to two-way dialogue and multi-directional group interaction, progressively shifting toward student-centered learning; (2) the teaching approach is communicative, emphasizing direct practice through hiwār (dialogue), group discussions, and collaborative tasks; (3) major challenges include students' heterogeneous prior knowledge, dominance of the mother tongue, time constraints, and psychological barriers such as language anxiety. The novelty of this study lies in its empirical investigation of contextually adaptive interaction strategies within a pesantren, where Arabic is embedded in daily life through bi'ah lughawiyyah. These findings contribute a contextually grounded model of communicative interaction management for Arabic language pedagogy in Islamic boarding school settings.